Experience of psychoactive substance use in patients with psychiatric disorders - Barbara Gouget-Para; Alice Deschenau; Jean-Charles Leblanc; Armelle Seiler; Fathia Djellil; Valérie Cerboneschi; Muriel Lascaux (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
A dual pathology is the coexistence of a psychiatric disorder and an addiction in the same patient. Between 30 and 50% of patients currently admitted to psychiatry in Europe would suffer from a dual pathology. The interaction between two mental illnesses can lead to a different clinical picture of the clinical pictures of each of the pathologies taken separately and may require new therapeutic strategies. The aim of this study was to better understand the decompensation or relapse of a dual pathology.  Based on a mixed quantitative and qualitative approach by grounded theory, adult patients hospitalized in psychiatry were asked about their subjective experience of the use of psychoactive substances. The sample consisted of sixteen patients, dependent on at least one psychoactive substance (tobacco excluded) and classified according to their psychiatric pathology: troubles of the schizophrenia spectrum, mood and personality disorders (respectively 7, 5 and 4 patients).  Results showed that therapeutic dimension of motivation to consume predominates hedonic and social dimensions, especially in schizophrenic patients. Although perceiving adverse effects of drugs, patients have the perception that their consumptions satisfy their expectations of products, especially in terms of appeasing their suffering. Most patients do not wish to enter a weaning process. Results suggested that decompensation of a dual pathology is often associated with a change in substance use, an acutization of psychotic experiences and an unfavorable social and emotional context that puts patients in critical condition requiring hospitalization in psychiatry.